Acanthamoeba keratitis: experience in a non-specialist microbiology laboratory. Issue 8 (August 1991) - Anderson, D; Soo, S S; Towler, H
Abstract : Acanthamoeba keratitis is an unusual complication of wearing soft contact lenses: a case was diagnosed by culturing corneal scrapings. Acanthamoeba are tolerant of variations in osmolarity in the culture media. Page's saline, recommended for culture agar plates, can easily be substituted with salines which are suitable for cell culture media, thereby avoiding the cumbersome manufacture of special saline. Early diagnosis as a result of successful isolation may avoid the need for keratoplasty.